(untitled) (Al-Mansour Journal, 2025)
This research aims to study the relationship between organizational Creation and academic entrepreneurship by surveying a sample of 50 faculty members at the College of Tourism Sciences, Al-Mustansiriya University. The research employs a descriptive analytical approach to analyze the impact of organizational Creation on fostering a culture of academic entrepreneurship within the university environment. The study concluded that organizational Creation positively influences academic entrepreneurship, revealing that flexible organizational structures, university leadership support, and the availability of financial and technological resources are key factors in promoting entrepreneurial thinking among faculty members. The results also highlighted several challenges hindering the adoption of academic entrepreneurship, most notably administrative bureaucracy, limited funding, and the lack of effective partnerships between universities and the tourism sector. The research recommends strengthening organizational Creation within universities by providing a supportive organizational environment, developing incentive policies to encourage faculty members to transform their research into entrepreneurial projects, and establishing university business incubators to facilitate the transfer of knowledge to the market.